2010
DOI: 10.1007/s00701-010-0683-9
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of ruptured dissecting vertebral artery aneurysms—long-term follow-up results, benefits of early embolization, and predictors of outcome

Abstract: In our experience, internal trapping of the dissected segment with a coil was straightforward, applicable to most patients, prevented rebleeding safely and effectively without significant procedural complications, and had a good follow-up outcome. The low Hunt-Hess grade remained predictors of favorable clinical outcomes. The timing of embolization did not significantly affect clinical outcome but early embolization reduces inpatient stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 28 publications
5
56
0
Order By: Relevance
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past 10 years, there have been a significant number of investigations into the feasibility of this technique [1][2][3][4][5][6][7][8][9][10]. Some articles have described the stability of occlusions treated with detachable coils and the efficacy of providing protection against VAD recurrence and consequent bleeding [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical treatment includes trapping the aneurysm, proximal ligation of the vertebral artery (VA ), or wrapping the aneurysm. Previous reports have suggested that endovascular parent artery occlusion is a safe and effective treatment for VAD [1][2][3][4][5][6][7][8][9][10]. Although some case series have reported on the feasibility of stent replacement, endovascular internal trapping has been performed in most of the cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in keeping with the published results of others. [24][25][26][27][28][29] A single patient in our series demonstrated immediate persistent filling of the ruptured pseudoaneurysm after proximal PVO. Importantly, the dissected vessel segment involved the origin of the PICA.…”
Section: Dissecting-type Vertebral Artery Pseudoaneurysms Presenting mentioning
confidence: 65%
“…[1][2][3][4][5][6][7] Although there have been recent reports documenting the effectiveness of stent-assisted coil embolization or flow diverter stent placement, [8][9][10] but parent artery occlusion remains as a safe and effective treatment, particularly in the acute phase of rupture. 11,12) To minimize the risk of re-hemorrhage and developing cerebral infarction following parent artery occlusion, it is important to make a strategy based on the location of the lesion relating to the posterior inferior cerebellar artery (PICA) origin.…”
Section: Introductionmentioning
confidence: 99%